Correlation of tumor necrosis factor-β and interleukin-1 gene cluster polymorphism with susceptibility to bacteremia in patients undergoing kidney transplantation - WU, Xiao-xia; WAN, Qi-quan; YE, Qi-fa; ZHOU, Jian-dang (Chinese medical journal, 2013)
Background Bacteremia remains a significant cause of morbidity and mortality after kidney transplantation. This study was conducted to investigate whether the polymorphisms of tumor necrosis factor （TNF）-β, interleukin （IL）-1β, and IL-1 receptor antagonist （IL-lra） gene predicted the susceptibility to bacteremia within the first 6 months after kidney transplantation. Methods Subjects comprised 82 infected kidney transplant recipients and 60 non-infected kidney transplant recipients. Bacteremia was diagnosed in 16 of the 82 infected recipients. Genomic DNA from these 142 kidney transplant recipients was extracted from peripheral blood leukocytes. Regions containing the Ncol polymorphic site at position ＋252 of TNF-β gene and the Aval polymorphic site at position -511 of IL-Iβ gene were amplified by polymerase chain reaction （PCR） and subsequently digested with Ncol and Aval restriction enzymes, respectively. The polymorphic regions within intron 2 of IL-lra gene containing variable numbers of a tandem repeat （VNTR） of 86 base pairs were amplified by PCR. Results Genotypic and allelic frequencies were similar between infected recipients and non-infected ones. Individual locus analysis showed that recipient TNF-β and IL-lra gene polymorphisms were not associated with the presence of bacteremia （P=0.684 and P=0.567, respectively）. However, genotype analysis revealed that recipient IL-1β 511CC genotype was strongly associated with susceptibility to develop bacteremia （P=0.003）. Recipient IL-1β-511CC genotype （odds ratio 5.242, 95% confidence intervals 1.645-16.706, P=0.005） independently predicted the risk for bacteremia within the first 6 months after kidney transplantation. Conclusions These findings indicate a critical role of IL-1β gene polymorphisms in susceptibility to bacteremia after kidney transplantation, which may be useful to screen for patients at higher risk for post-transplant bacteremias. Thus, the identified individuals can benefit from preventive treatment and a less potent immunosuppressive regimen.